2015
DOI: 10.17736/ijope.2015.jc647
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Elastic Modulus of Hydrate-Bearing Sediments

Abstract: A model for the elastic modulus of hydrate-bearing sediment (HBS) is presented considering the variation of the hydrate saturation and hydrate occurrence mode. The model is based on the classical series and parallel modes, introducing a parameter of statistical force transfer paths among particles in HBS. Macro-triaxial compression tests and micro X-ray computed tomography (CT) observations of HBS in the gas-saturated formation mode were conducted. The applicability of the model was checked through the compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…In nature, GHBS consists of four components, i.e., soil/rock skeleton, GH, water, and gas [7]. Triaxial compression tests were conducted when GH formed in pores of the specimen under a non-dissociation condition, simulating the mechanical behavior before GH exploitation [8][9][10][11][12][13][14][15]. The results indicated that: different GHBS preparation methods such as gas saturated method and water saturated method lead to obvious differences in the mechanical behavior; the GH existence mode in the pores of sediments varies with the increase of GH saturation, leading to the transition of the deformation from shear shrinkage to shear dilatancy.…”
Section: Introductionmentioning
confidence: 99%
“…In nature, GHBS consists of four components, i.e., soil/rock skeleton, GH, water, and gas [7]. Triaxial compression tests were conducted when GH formed in pores of the specimen under a non-dissociation condition, simulating the mechanical behavior before GH exploitation [8][9][10][11][12][13][14][15]. The results indicated that: different GHBS preparation methods such as gas saturated method and water saturated method lead to obvious differences in the mechanical behavior; the GH existence mode in the pores of sediments varies with the increase of GH saturation, leading to the transition of the deformation from shear shrinkage to shear dilatancy.…”
Section: Introductionmentioning
confidence: 99%
“…In the lab experiments, it has been found that the increasing hydrate saturation alters the formation deformation from the shear shrinkage to shear dilatancy. [45][46][47] It is because that the little presence of hydrate cannot affect the formation strength. 41 The low hydrate concentration in the sediment means that the soil is the major content in the rock skeleton, which makes the sand particles and the cementation between particles bear the most shear stress.…”
Section: Effect Of Hydrate Saturationmentioning
confidence: 99%
“…The common triaxial tests in the lab conditions use the NGH samples in the static nondissociation conditions. [46][47][48][49] Not just the static hydrate can affect the mechanical behavior, the dynamic change of NGH cannot be ignored. The dynamic change of NGH can help to develop natural gas resources but can cause the sand production problem, like the two sides of the coin.…”
Section: Effect Of Hydrate Dissociationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several models have been proposed to formulate the stress‐strain relationship of GHBS . The elastic modulus of gas hydrate‐bearing coarse sand is formulated by series and parallel model, and the shear strength of tetrahydrofuran hydrate‐bearing clay is analyzed on the basis of the Mohr‐Coulomb and Drucker‐Prager criterion . The Duncan‐Chang model is applied to simulate the nonlinear elastic behavior of GHBS .…”
Section: Introductionmentioning
confidence: 99%